2016
DOI: 10.1038/srep38934
|View full text |Cite
|
Sign up to set email alerts
|

Shengmai Formula suppressed over-activated Ras/MAPK pathway in C. elegans by opening mitochondrial permeability transition pore via regulating cyclophilin D

Abstract: Since about 30% of all human cancers contain mutationally activated Ras, down regulating the over-activation of Ras/MAPK pathway represents a viable approach for treating cancers. Over-activation of Ras/MAPK pathway is accompanied by accumulation of reactive oxygen species (ROS). One approach for developing anti-cancer drugs is to target ROS production and their accumulation. To test this idea, we have employed C. elegans of let-60 (gf) mutant, which contain over-activated let-60 (the homolog of mammalian ras)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…We used NAC at 9 mM, a concentration that has been shown to lower ROS [55] but has no effect on wild type viability [52]. Like other studies using prooxidants on let-60rasgf mutants [28], we found that although PQ had no effect on vulva formation in the wild type, it partially suppressed the Muv phenotype of let-60rasgf ( Fig 1D). Conversely, we found that NAC treatment had no effect on the wild type but enhanced the Muv phenotype of let-60rasgf ( Fig 1D).…”
Section: Ras Signalling Is Sensitive To Rossupporting
confidence: 60%
See 1 more Smart Citation
“…We used NAC at 9 mM, a concentration that has been shown to lower ROS [55] but has no effect on wild type viability [52]. Like other studies using prooxidants on let-60rasgf mutants [28], we found that although PQ had no effect on vulva formation in the wild type, it partially suppressed the Muv phenotype of let-60rasgf ( Fig 1D). Conversely, we found that NAC treatment had no effect on the wild type but enhanced the Muv phenotype of let-60rasgf ( Fig 1D).…”
Section: Ras Signalling Is Sensitive To Rossupporting
confidence: 60%
“…One of the ways ROS can participate in signalling, is by modulating the activities of small GTPases. For examples, the Ras signalling pathway is known to be modulated by ROS in mammals [26,27] and C. elegans [4,28]. One of the ways the RAS pathway is affected by ROS in mammals is by direct oxidation of a sensitive cysteine (C118) of the RAS protein itself, by nitric oxide (NO) and superoxide [29,30] as well as by hydrogen peroxide in the presence of transition metals [31].…”
Section: •-mentioning
confidence: 99%
“…MAPK activation promotes cancer progression and resistance to chemotherapeutic drugs [30,31]. On the contrary, inhibition of MAPK pathway inhibits tumor metastasis and tumor-related angiogenesis [32,33]. However, studies of MAPK pathway in EC have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The mPTP activity mainly appeared as a property of mammalian and yeast mitochondria, where it was intensively investigated. However recently the mPTP was also reported in mussel [ 183 ], in sea urchin oocytes [ 184 ], in the nematode Caenorhabditis elegans [ 185 ], in plathelminths [ 186 ] and insects [ 187 , 188 ], while it is still controversial in crustaceans [ 189 , 190 ]. Indeed, it is not a “vertebrate invention” to rule cell fate, as initially thought [ 191 ].…”
Section: Overview Of the F 1 F O mentioning
confidence: 99%